Place: Interactive Learning Media Augmented Reality (AR) 3d In “Plant Cell” for 11th Grade Students - Nugraha, Adimas Nanda; Pramudita, Dias Aziz (Proceedings International Conference on Education Innovation and Social Science, 2022)
The era development, the rapid of technology, and the availability of mobile phone use for students in facilitating learning should be accompanied by familiarization of the use of media as one to support the learning. Biology is considered as a subject that requires more understanding and interpretation through its visualization. Moreover, the one focuses on “Plant Cell” material is rare. This research is further aimed at: (1) developing an interactive learning media Augmented Reality (AR) 3D in Biology material "Plant Cell" for11th grade students, (2) conducting the feasibility test of the interactive learning media, and (3) examining the effectiveness of the interactive learning media. Research and Development (R&D) was employed, and ADDIE model was adapted. The participants were 20 students. Questionnaires were utilized as the instruments. The steps in developing the media included: Needs Analysis, Design Making, Design Implementation, Alpha Testing, Revision, Beta Testing, and Media Improvement. Next, validity test and reliability test from two experts were conducted. The results of the research reveal: (1) validity test by using Aiken V was in the medium (0,5-0,75) and high category (0,875), and reliability test was in the perfect category (0,961), (2) the media effectiveness level by using Aiken V was in the medium category (0,73), and by using SUS was acceptable (71-100), and margin high (51-62). In this research, last, the suggestions in the form of some revisions to the media were provided.